Protective Effects of Pioglitazone on Dextran Sodium Sulphate-Induced Colitis in Rats: Effects of Pioglitazone on Dextran Sodium Sulphate-Induced Colitis - Awdan, Sally El; E. Mostafa, Rasha (Iranian Journal of Pharmaceutical Sciences, 2018)
The aim of the present study is to investigate the preventive effect of pioglitazone on colitis induced with dextran sulfate sodium (DSS) in rats. Twenty-four male Sprague-Dawley rats weighing 180-200 g were randomized into four groups. Rats of the 1st group received only saline and served as normal group. Colitis was induced in the remaining 3 groups by 1.5% DSS administered in drinking water for 8 days. Group 2 received only saline p.o. for 30 days and served as DSS control group. Groups 3 and 4 received pioglitazone (PIO; 10 mg/kg/day, p.o.) and sulfasalazine (SUL; 300 mg/kg) respectively for 30 days. All animals were sacrificed 24 h after the last treatment. Serum levels of interleukin-2 (IL-2), interleukin-6 (IL-6), and interleukin-17 (IL-17) were measured. Levels of tumor necrosis factor-α (TNF-α), reduced glutathione (GSH) and malondialdhyde (MDA), were measured in colon tissue. Significant elevation in GSH levels and reduction in MDA and TNF-α levels in colon tissue were observed in pioglitazone and sulfasalazine treated group when compared with the DSS control group. Significant elevation in serum IL-2 and reduction in serum IL-6 and IL-17 were observed when compared with the DSS control group. Pioglitazone reduced DSS-induced colitis possibly via reduction of MDA, TNF-α, IL-6, and IL-17 levels.